Affordances perspective and grammaticalization: Incorporation of language, environment and users in the model of semantic paths - Andrason, Alexander; Visser, Marianna (Studies in Second Language Learning and Teaching, 2015)
The present paper demonstrates that insights from the affordances perspective can contribute to developing a more comprehensive model of grammaticalization. The authors argue that the grammaticalization process is afforded differently depending on the values of three contributing parameters: the factor (schematized as a qualitative-quantitative map or a wave of a gram), environment (understood as the structure of the stream along which the gram travels), and actor (narrowed to certain cognitive-epistemological capacities of the users, in particular to the fact of being a native speaker). By relating grammaticalization to these three parameters and by connecting it to the theory of optimization, the proposed model offers a better approximation to realistic cases of grammaticalization: The actor and environment are overtly incorporated into the model and divergences from canonical grammaticalization paths are both tolerated and explicable.